Propagation of Light in a Space Filled with an Electromagnetic Medium - Rozov, Andrey (Transactions on Engineering and Computing Sciences, 2023)
The features of light propagation in outer space filled with an electromagnetic medium, the physical model of which was proposed in a previous article [A. Rozov, Z. Naturforsch. 72, 757 (2017)] are analyzed. This model made it possible to derive the equations of electrodynamics for moving media within the frame of classical mechanics. Joint analysis of the electromagnetic medium model and electrodynamic equations taking into account known data and astronomical observations of galaxy redshift and cosmic background radiation allowed to make some conclusions both about the internal structure of the electromagnetic medium and on the peculiarities of light propagation in outer space.